Applying different techniques for evaluating the resistance to moisture of electrospun PVA nanofibers - Alessandro Estarque de Oliveira; Mônica Lopes Aguiar; Vádila Giovana Guerra (The Journal of Engineering and Exact Sciences)
Poly (Vinyl Alcohol) (PVA) is used to produce nanofibers with electrospinning for several applications related to the non-toxicity of the material, however, the application in air filtration in hindered by the high hydrophilicity of the material, which requires the crosslinking with additives. In this work, different techniques were assessed to verify the moisture resistance of PVA nanofibers crosslinked with citric acid. The mass loss did not reveal significant structural modification of the filter media due to the relatively low mass of the nanofibers in comparison to the mass of the substrate, proving the poor applicability of this technique for this process. The measurement of the water contact angle was not suitable for the experimental circumstances as well. A methodology was then purposed, measuring the pressure drop before and after the flow of clean air stream (~15.0 cm s-1) through the filter media with different contents of water (49, 68, and 90% R.H.) to verify the humidity resistance of the fibers over time (zero to 60 min). The samples were resistant to humidity and no significant structural changes occurred in the fibers after the process in accordance with analysis of scanning electron microscopy images. For the two lowest humidities, variation of the pressure drop was equal to approximately zero after 60 min while it achieved 4.1% for 90% R.H. This methodology proved to be suitable for air filtration application.